2018
DOI: 10.1002/gps.5014
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the risk factors of grief and burden in caregivers of persons with dementia: Multivariate analysis

Abstract: Background Caregivers of persons with dementia (PWD) can experience loss and grief long before the death of the person. While such phenomenon of pre‐death grief (PDG) has been increasingly described, we are uncertain how it can be distinct from the well‐studied construct of caregiver burden. Objective To determine whether there are differences in the risk factors of PDG and caregiver burden to aid in our understanding of the relationship between the two constructs. Methods Spouses or children of community‐dwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…As seen in this study, burden (not grief) leads to poorer physical health in caregivers. In the course of providing care, family caregivers are faced with a myriad of physical care demands, 7,18,21 which may result in subjective perception of burden, 18 as well as manifest with the consequence of poorer physical health. 22 In contrast, grief (not burden) leads to poorer perception on the PAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in this study, burden (not grief) leads to poorer physical health in caregivers. In the course of providing care, family caregivers are faced with a myriad of physical care demands, 7,18,21 which may result in subjective perception of burden, 18 as well as manifest with the consequence of poorer physical health. 22 In contrast, grief (not burden) leads to poorer perception on the PAC.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although caregiver grief may share some common risk factors with caregiver burden (such as later stage of dementia, behavioral problems in PWD, and primary caregiving role), there are also several risk factors that are unique to grief and differentiate grief from burden, including younger age of PWD, lower educational attainment of caregivers, and spousal caregiver. 7 In addition, caregiver grief has an independent effect (which is separate from that of burden) on the adverse outcome of caregiver depression. 3 It also has a synergistic relationship with caregiver burden, with high grief further amplifying the effect of burden on caregiver depression.…”
Section: Introductionmentioning
confidence: 99%
“…While the key factors from this study bear some semblance to the risk factors of caregiver burden, the factors associated with grief and burden are not necessarily synonymous. This is reflected in a recent study [13], which demonstrated the shared risk factors between grief and burden (such as behavioral problems in PWD; and high amount of caregiving duties), as well as the differences in risk factors between them (for example, spousal caregiver was associated with grief but not burden; and severe stage of dementia was more strongly associated with grief than burden).…”
Section: Discussionmentioning
confidence: 97%
“…Notably, grief-related interventions are distinct from those used to address caregiver burden in existing dementia services (where the focus is on reducing the perceived burden of caregivers and improving their coping skills; as guided by the transactional model of stress and coping) [23]. Grief-related interventions are more geared towards addressing the emotions, perceptions and behaviors related to losses [8, 13]. They may include facilitating caregivers to revisit the loss and its associated emotions [24, 25], reconstruct the meaning of the loss [26], find continual connection with the lost relationship [25, 27], involve the whole family in the grieving process [26, 28] and adjust to life changes following the loss [24, 25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation